(untitled) (Journal of Health, Population and Nutrition, 2013)
It is not clear what effect socioeconomic factors have on adherence to antiretroviral therapy (ART) among patients in low- and middle-income countries. We performed a systematic review of the association of socioeconomic status (SES) with adherence to treatment of patients with HIV/AIDS in low- and middleincome countries. We searched electronic databases to identify studies concerning SES and HIV/AIDS and collected data on the association between various determinants of SES (income, education, occupation) and adherence to ART in low- and middle-income countries. From 252 potentially-relevant articles initially identified, 62 original studies were reviewed in detail, which contained data evaluating the association between SES and adherence to treatment of patients with HIV/AIDS. Income, level of education, and employment/occupational status were significantly and positively associated with the level of adherence in 15 studies (41.7%), 10 studies (20.4%), and 3 studies (11.1%) respectively out of 36, 49, and 27 studies reviewed. One study for income, four studies for education, and two studies for employment found a negative and significant association with adherence to ART. However, the aforementioned SES determinants were not found to be significantly associated with adherence in relation to 20 income-related (55.6%), 35 education-related (71.4%), 23 employment/occupational status-related (81.5%), and 2 SES-related (100%) studies. The systematic review of the available evidence does not provide conclusive support for the existence of a clear association between SES and adherence to ART among adult patients infected with HIV/ AIDS in low- and middle-income countries. There seems to be a positive trend among components of SES (income, education, employment status) and adherence to antiretroviral therapy in many of the reviewed studies. J HEALTH POPUL NUTR 2013 Jun; 31(2): 150-170 DOI: http://dx.doi.org/10.3329/jhpn.v31i2.16379